Dentist's Responsibility for Improper Implementation of Informed Consent - Kurniawan, R Veryanto; Sutarno, Sutarno; Nugroho, Hari Pudjo (Rechtsvinding, 2025)
The purpose of this study is to analyze the application of informed consent to dentists' responsibilities under civil law and to analyze the application of informed consent to dentists' responsibilities under criminal law. This study falls into the category of normative legal research. The research approaches used consist of a legislative approach, a comparative approach, and a conceptual approach. The findings in this study indicate that the implementation of informed consent, in the context of civil liability, reflects the application of contractual principles in the professional relationship between dentists and patients. This relationship is based on a valid agreement as stipulated in Article 1320 of the Indonesian Civil Code (KUHPerdata). This study also shows that without valid consent from the patient, medical actions performed by dentists may lose their legal justification and, from a juridical perspective, can be classified as unlawful acts, such as abuse or negligence resulting in criminal consequences. This is in line with the provisions of Article 440 of Law Number 17 of 2023 concerning Health, which regulates criminal sanctions for medical personnel whose negligence causes serious injury or death. This provision is further strengthened by the general provisions in Articles 466 to 469 of Law Number 1 of 2023 concerning the Criminal Code (KUHP) which regulates criminal acts against the human body.